Involvement of oxidative stress in tri-ortho–cresyl phosphate-induced liver injury in male mice. (October 2016) - Xu, LL; Long, CY; Wang, JL; Yu, M; Chen, JX
Tri- ortho –cresyl phosphate (TOCP) has been widely used as plasticizers, plastic softeners, and flame retardants in industry and reported to have delayed neurotoxicity and reproductive toxicology in animals. However, it remains to be elusive whether TOCP induces liver injury. In this study, male mice were orally administered different concentrations of TOCP (100, 200, or 400 mg/kg/day) for 28 days. Histological examination showed that TOCP led to serious hepatocellular injury. In addition, administration of TOCP induced a marked elevation in the serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in mice. The content of malondialdehyde (MDA) was increased significantly in the liver after the mice were treated with TOCP; while there was a dramatic decrease in the content of glutathione (GSH) and the activities of antioxidative enzymes superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX). TOCP inhibited viability of mouse liver cancer Hepa 1-6 cells in a dose-dependent manner. Meanwhile, TOCP significantly increased MDA content and inhibited GSH content and the activities of SOD and GSH-PX in the cells, respectively. Oxidative stress dramatically inhibited viability of Hepa 1-6 cells; while inhibition of oxidative stress by N -acetyl-l -cysteine could rescue the cell viability inhibited by TOCP to a certain extent. In summary, oxidative stress might be involved in TOCP-induced hepatocellular injury in male mice.